AB0882 Efficacy of intralesionnal sodium thiosulfate in disabling tumoral calcinosis: about two cases. (15th June 2017) - Goossens, J; Courbebaisse, M; Ratsimbazafy, V; Bazin, D; Daudon, M; Frochot, V; Richette, P; Lioté, F; Ea, H-K; Guigonis, V
Abstract : Background: Tumoral Calcinosis (TC) is a difficult-to-treat complication that can occur during the course of several diseases such as dermatomyositis or genetic hyperphosphatemia. It is a painful and disabling condition that can give rise to local complications including joint mobility reduction, cutaneous ulceration and superinfection. Until now, many treatments have been used with inconstant efficacy. Objectives: Intravenous sodium thiosulfate gives promising results in calciphylaxis and ectopic calcifications, and intra-lesional injections could be effective for tumoral calcinosis. Methods: We report two cases of successful intra-lesional injections of sodium thiosulfate (STS). Results: Case 1: A 44-years old woman, with history of dermatomyositis developed in 2009 several TC involving the extensor surfaces of the right elbow and forearm, the two ischiatic regions, fingers and lumbar back. As TC kept growing despite successive treatments, including intravenous STS, we proposed weekly intra-lesional injections of 10% STS in the elbow's lesion. The injected volume varied from 10 to 30 mL at each session. Fourrier transform infrared spectroscopy (FTIR) of the aspirations confirmed that TC was composed of carbonated-apatite crystals. After 6-month treatment, we observed clinical and radiological regression of elbow TC whereas bottom TC and finger calcifications were unchanged (Fig 1 ). No side effect was observed except a subcutaneous infection occurring after an injection during the fifth month. This infection resolved with anti-staphycoccal antibiotics. Calcium, bicarbonate and chlorus serum levels, anion gap and eGFR remained unchanged during STS treatment. Case 2: A 42-year old male presented with a prolonged history of hyperphosphatemic familial TC, confirmed by genetic analysis revealing homozygous mutations in the gene encoding the fibroblast growth factor 23. The extraosseous calcifications comprised a plain lesion on the right side of the left tibia and a massive heterogeneous lesion in the right buttock, making it the sitting position impossible. Treatment with maximal dose of phosphate binders, diet prescription and an attempt to surgically remove of the buttock's lesion were unsuccessful. Topical application of STS led to a near complete disappearance of the tibial lesion but was inefficient to treat the TC at the buttock. Considering the potential efficacy of STS in this patient, local injections of 25% STS (12 mL every week) were performed. The calcified material aspiration's analysis confirmed that TC was composed of carbonated-apatite crystals. Calcium and bicarbonate serum levels, anion gap and eGFR remained unchanged. After a 12-month treatment of STS injections, the lesion had significantly regressed (Fig 2), allowing the patient to sit again with no pain. Conclusions: Intra-lesional injection of STS seems to be a promising treatment for TC. More studies are needed to confirm these results, and to understand the mechanisms implicated in the calcinosis resorption. Disclosure of Interest: None declared